A Control Method for Modified Bidirectional Cuk DC-DC Converter - Azmi, Muhammad Rifqi; Dahono, Andriazis; Ilman, Sofyan M.; Rizqiawan, Arwindra; Dahono, Pekik A. (Universitas Negeri Malang, 2021)
A control method for a modified bidirectional Cuk DC-DC converter is proposed in this paper. The proposed controller is a double control loop consisting of an inner current control loop and a voltage control loop is used to control the converter. The small-signals model that is useful in designing controllers is derived in this paper. A simple PI controller is used for both controllers. The simulation and experimental results are included in this paper to validate the performance of the proposed controller.